1970
DOI: 10.1111/j.1464-410x.1970.tb04483.x
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Activity of the Paraurethral and Perineal Muscles in Normal and Pathological Conditions

Abstract: THE excellent recent studies of Tanagho and Smith (1966), Hutch (1967), Woodburne (1968) andGil Vernet (1964) have clarified many problems about continence and micturition. However neither the micro-anatomical details of the course of the fibres of the external urethral sphincter nor its exact part in urinary continence and micturition are yet solved in a definite manner.Our working hypothesis is that urinary continence and voiding are controlled in the urethra by 3 complementary factors: the visco-elastic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 14 publications
(12 reference statements)
4
34
0
Order By: Relevance
“…These problems become less significant with increasing severity of neuro pathology, so that while with incomplete lesions a random-EMG of the pelvic floor is sufficient to document the activity of the external sphincter, in incomplete lesions of any aetiology a separate evaluation of the peri urethral striated EMG and anal sphincter EMG is advisable (Vereecken and Verduyn, 1970;Perkash, 1980). Uroflowometry and pressure profiles (Sunder et al, 1978;Clarke and Thomas, 1981), as single investigations are useful to understand the underlying pathophysiology but are of limited diagnostic clinical value for paraplegics.…”
Section: Discussionmentioning
confidence: 99%
“…These problems become less significant with increasing severity of neuro pathology, so that while with incomplete lesions a random-EMG of the pelvic floor is sufficient to document the activity of the external sphincter, in incomplete lesions of any aetiology a separate evaluation of the peri urethral striated EMG and anal sphincter EMG is advisable (Vereecken and Verduyn, 1970;Perkash, 1980). Uroflowometry and pressure profiles (Sunder et al, 1978;Clarke and Thomas, 1981), as single investigations are useful to understand the underlying pathophysiology but are of limited diagnostic clinical value for paraplegics.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of several studies have speculated that a dysfunction of the posterior urethra at the end of micturition could cause PMD [10]. Feneley [11] and Vereecken and Verduyn [12] postulate a failure of the bulbospongiosus muscle or pelvic floor, its insufficiency causing the impossibility to generate higher intracavernous pressure, a failure of ejaculation force [13], and the loss of the postvoid milking reflex. They state that this results in an inadequate drainage of urine, which has pooled and become trapped in the bulbar urethra after voiding [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that inserting examining fingers in anus for anal stretch caused marked inhibition of the electromyogram (EMG) activity in both EUS and EAS (48). In ablebodied persons, EMG recording from the EUS and EAS during micturition and cystometry also showed simultaneous electric activity in these muscles (1,50,62). Results coming from clinical studies suggested anal stretch could be a useful technique to facilitate voiding in overactive urethra sphincter patients (15,36,38).…”
mentioning
confidence: 99%